Parental Perceptions of Deworming vis-à-vis Children’s Activity Level, Appetite, and Eating Patterns as Indicators of Nutritional Well-being in the Municipality of Buug, Zamboanga Sibugay, Philippines - Breathny A Cabahug; Cherrgie Mae B Caong; Reynald M Hisona; Robelyn A Saga; Tashmera D Laranjo; Christy L Taruc; Maricel L Tercio; Randy Ian Ferenal Gallego (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2025)
Intestinal parasitic infections remain a persistent public health problem in low-resource settings, contributing significantly to childhood malnutrition. Deworming programs have been recognized as an effective strategy to enhance nutrient absorption, promote child growth, and improve overall health. However, parental perceptions influence the uptake and success of these interventions. This study aimed to assess parents’ perceptions of the role of deworming in controlling malnutrition among school-aged children. A descriptive-correlational design was employed among 104 parents or guardians of school-aged children enrolled in two public elementary schools in Buug, Zamboanga Sibugay, Philippines, who were recipients of local and national deworming programs. Data were collected using a validity- and reliability-tested questionnaire (CVR = 0.5 to 0.9; Cronbach’s alpha = 0.75) and analyzed using frequency, percentage, standard deviation, and correlation analyses, including Spearman’s rho and Pearson’s r. At a 0.05 level of significance, improvement in children’s activity levels was significantly associated with parental sex (p = 0.007) and employment status (p = 0.003). Improvement in children’s appetite and eating patterns was very significant related to parental employment status (p = 0.006) and number of children in the household (p = 0.021). These findings highlight how sociodemographic factors influence parental perceptions of deworming outcomes, underscoring the need for targeted education and community awareness initiatives to enhance the acceptance and effectiveness of deworming programs as a public health strategy for combating malnutrition.